Acute Ischemic Stroke in Moyamoya Disease: A Case Report - Kustila, Ela (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Introduction: Moyamoya disease (MMD) is also known as spontaneous occlusion of the circle of Willis, is a chronic, occlusive cerebrovascular disease with an unknown etiology.1 It is characterized by progressive stenosis or occlusions of the intracranial internal carotid artery (IAC) and or the proximal portion of the anterior cerebral artery (ACA) and middle cerebri artery (MCA).1,2 This steno-occlusive pattern is associated with a compensatory development of a collateral network of vessels at the base of the brain, appearing as a “puff of smoke” on conventional angiography ( “moyamoya” in Japanese).1,2 The clinical presentations of MMD include transient ischemic attacks, ischemic strokes, hemorrhagic strokes, seizure, headache, and cognitive impairment.1,2,3 Case Report: This case study presents a 48-year-old male with symptoms hemiparesis sinistra. Brain CT scan result was subacute infarct at right anterior cerebri artery territory. Digital Substract Angiography (DSA) result was occlusion in the right media cerebri artery (MCA) and right anterior cerebri artery (ACA), severe stenosis right verterbral artery until basilar artery, moyamoya vessels at anterior and posterior circulation.